Is it all in your head? : true stories of imaginary illness - O'Sullivan, Suzanne (Other Press, 2015)
"A neurologist delves into the often misunderstood world of psychosomatic disorders, sharing individual case histories of patients who have medically unexplained symptoms, and encourages people to look with compassion at the ways in which our brains act out and to question our failure to credit the intimate connection between mind and body,"--NoveList.